Analisis Technology Acceptance Model pada penggunaan website Prodamas Plus sebagai media informasi masyarakat - Andanuwari, Reo Aldo; Indana, Luthfi; Dewi, Shabrina Syntha (Journal of Information System and Application Development, 2023)
Prodamas is a community empowerment program initiated by the Mayor of Kediri in 2019. This program aims to improve people's welfare economically and socially. In 2021, Prodamas upgraded to Prodamas Plus to reach a wider field. The purpose of this study was to determine the effectiveness of a website created as an information media related to Prodamas Plus in Kediri City. The method used is the Technology Acceptance Model method with five variables including: perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use and actual system usage. The results of the study show that Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), and Behavioral Intention To Use (IU) simultaneously affect Actual System Usage (AU). So based on the results of this study it can be concluded that the use of the website is considered effective in conveying information to the people of Kediri City.